Poetic Form and the Nature of Aesthetic Communication in Ancient Critical Discourse - Al-Arfi, Nassiba (Arts for Linguistic & Literary Studies, 2025)
This study explores the poetic form and aesthetic communication in ancient critical discourse, a key issue in classical literary criticism. Ancient critics examined the linguistic elements of poetic expression, viewing poetry as a language with artistic, aesthetic, social, and ethical dimensions. They perceived aesthetic communication as a process of stimulation, influence, and pleasure, emphasizing the functional role of poetic imagination in both creation and reception. Understanding poetry, therefore, hinges on grasping the imaginative vision conveyed by the poet. The research is structured into four sections: the centrality of poetic function in ancient rhetoric, the aesthetic role of poetic form, the audience’s engagement with poetic communication, and the readiness for expression based on audience type. The study concludes by distinguishing between poetry’s functional role in directive discourse and its intrinsic aesthetic purpose. It also underscores the depth of analytical and critical thought achieved by ancient critics in evaluating aesthetic communication across various cultural contexts.